2014
DOI: 10.1002/da.22329
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Antidepressants in Pediatric Anxiety Disorders: A Systematic Review and Meta-Analysis

Abstract: Background Randomized, controlled trials have demonstrated that antidepressants are efficacious in the treatment of anxiety disorders in youth. However, there are no recent, systematic analyses of the efficacy, safety or tolerability of these medications in pediatric anxiety disorders. With this in mind, we sought to systematically review and conduct a meta-analysis of double-blind, placebo-controlled-trials of antidepressants in these conditions. Methods A systematic review and meta-analysis of prospective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 47 publications
5
132
0
Order By: Relevance
“…Importantly, given this difference and that recent trials of SSNRIs and SSRIs have (1) utilized similar parallel-group designs, (2) have been collected within a more recent time period, and (3) all used Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) (American Psychiatric Association 1994) criteria for the anxiety disorders, we utilized this relative homogeneity in design and population to perform several post hoc analyses. Among these trials (n = 9), the effect size (Strawn et al 2015b) decreases with time (R 2 = -0.84, p = 0.004), although no association between the effect size (Cohen's d) and the number of study sites was found ( p = 0.547) (Fig. 2).…”
Section: Study Outcome and Placebo Response Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, given this difference and that recent trials of SSNRIs and SSRIs have (1) utilized similar parallel-group designs, (2) have been collected within a more recent time period, and (3) all used Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) (American Psychiatric Association 1994) criteria for the anxiety disorders, we utilized this relative homogeneity in design and population to perform several post hoc analyses. Among these trials (n = 9), the effect size (Strawn et al 2015b) decreases with time (R 2 = -0.84, p = 0.004), although no association between the effect size (Cohen's d) and the number of study sites was found ( p = 0.547) (Fig. 2).…”
Section: Study Outcome and Placebo Response Ratementioning
confidence: 99%
“…The effect size of selective serotonin reuptake inhibitors (SSRIs) and selective serotonin norepinephrine reuptake inhibitors (SSNRIs) in randomized controlled trials of youth (Strawn et al 2015b) is not associated with the number of sites (A), but is related to the year of publication (B). Lines are shown for weighted least squares regression.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in contrast to data in TD youth, which support the use of both medications and therapy. [7][8][9] Most primary care providers lack specific training in managing youth with ASD and co-occurring psychiatric conditions. 10 On the basis of this finding, coupled with the lack of anxiety treatments for youth with ASD, the Anxiety Workgroup sought to develop a systematic approach to the assessment and treatment of anxiety that primary care providers use in their clinical practice.…”
mentioning
confidence: 99%
“…The term of "behavioural activation" which occurs at higher rates in paediatric patients than adults refers to; hyperactivity, impulsivity, insomnia or disinhibition and, importantly shows a distinct clinical pattern from treatment-emergent mania [22,23]. A metaanalysis including nine RCTs in children and adolescents showed that behavioural activation is strongly associated with antidepressant treatment compared to placebo [24]. Activation appears to be more common in prepubertal children with an average rate of 10.7% than in adolescents (2.1%) [25].…”
Section: Discussionmentioning
confidence: 99%